Retrospective Study of the Survival of Patients who Underwent Cardiopulmonary Resuscitation in an Intensive Care Unit - Moreira,Daniel Martins (2002)
OBJECTIVE: To evaluate clinical and evolutive characteristics of patients admitted in an intensive care unit after cardiopulmonary resuscitation, identifying prognostic survival factors.METHODS: A retrospective study of 136 patients admitted between 1995 and 1999 to an intensive care unit, evaluating clinical conditions, mechanisms and causes of cardiopulmonary arrest, and their relation to hospital mortality.RESULTS: A 76% mortality rate independent of age and sex was observed. Asystole was the most frequent mechanism of death, and seen in isolation pulmonary arrest was the least frequent. Cardiac failure, need for mechanical ventilation, cirrhosis and previous stroke were clinically significant (p<0.01) death factors.CONCLUSION: Prognostic factors supplement the doctor's decision as to whether or not a patient will benefit from cardiopulmonary resuscitation.